Pengaruh Current Ratio, Return on Asset, Debt to Asset Ratio dan Firm Size terhadap Price to Book Value (Pada Perusahaan Consumer Cyclicals Subsektor Apparel and Luxury Goods yang Terdaftar di Bursa Efek Indonesia Periode 2015-2023) - Surbakti, Ica Sinsa Br; Febryanti, Diah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study looks at the effects of firm size, debt to asset ratio, return on assets, and current ratio on price to book value in consumer cyclicals companies in the apparel and luxury goods subsector that are listed on the Indonesia Stock Exchange between 2015 and 2023. This study used a quantitative technique that is both descriptive and verifying. Secondary data was used, and quantitative data in the form of financial statements (annual reports) from the 2015–2023 annual reports of Consumer Cyclicals Sector Companies in the Apparel and Luxury Goods Subsector listed on the Indonesia Stock Exchange were used for data collection. According to the research's limited test results, the Price to Book Value is unaffected by the Current Ratio. Book value is unaffected by return on assets. The debt-to-asset ratio has no effect on price to book value, whereas firm size has a negative impact. The current ratio, return on assets, debt-to-asset ratio, and firm size all significantly affect price to book value, either separately or in combination, according to the simultaneous test research.